The Existence of Aesthetic Transformation in Traditional Batik Colors Based on the Review of Memetics Theory (Case Study: Traditional Batik in Tuban, East Java, Indonesia) - Ciptandi, Fajar; Arumsari, Arini (Harmonia: Journal of Arts Research and Education, 2024)
This article discusses the existence of aesthetics in traditional batik colors in Tuban, East Java, Indonesia, which is reflected in the appreciation of the deep values in the activity of making cloth. Batik colors have been one of the foundations for producing traditional identity values belonging to the Tuban community and have been preserved for generations. However, the existence of this aesthetic is gradually experiencing degradation due to some disruptions, such as modernity, trends, and technology, which has led to transformation. The purpose of the study is to interpret the relationship between the weakening of the existence of aesthetics in traditional Tuban batik colors and the daily behavior patterns of people in current conditions. The research method was conducted using a phenomenological approach, and it is reviewed based on the principle of memetics theory to find out the factors that cause this phenomenon. It is essential to produce a conclusion to enrich fundamental knowledge in understanding the causes of transformation in the aesthetic existence of a tradition so that it becomes the basis for consideration in taking transformative action to preserve the tradition.